The Effect of Increasing Fracture Site Stiffness on Bone–Pin Interface Stress and Foot Contact Pressure within the Equine Distal Limb Transfixation Cast: A Finite Element Analysis - Lescun, Timothy B.; Adams, Stephen B.; Nauman, Eric A.; Breur, Gert J. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to determine how increasing stiffness of fracture site tissues distal to the pins in an equine distal limb transfixation cast influences stress at the bone–pin interface, within the bones distal to the transcortical pins, and contact pressure between the foot and the cast.Study Design A transfixation cast finite element model was used to compare the bone–pin interface stress, pin stress, bone stress distal to the pins and contact pressure between the foot and the cast, using six stiffness values for a composite tissue block representing progressive stages of fracture healing.Results Increasing stiffness of the composite tissue block resulted in a decrease in the maximum stresses at the bone–pin interface, an increase in stresses distal to the transcortical pins and a decrease in the maximum pin stresses. As the composite tissue block stiffness was increased, contact pressure between the bottom of the composite tissue block and the cast increased and the stress patterns surrounding the pin holes became less focal.Conclusion The findings of this study illustrate that with good foot to cast contact within a transfixation cast, increases in tissue stiffness due to progressive fracture healing are expected to reduce bone-pin interface stresses, and increase fracture site loading and stress. Increasing the contact pressure between the foot and the cast could reduce transfixation casting complications such as pin loosening, pin hole fracture and poor fracture healing, if these results transfer to ex vivo and in vivo settings.
Keywords: transfixation casting; fracture healing; horse; pin stress; finite element analysis